Elections and Market Provision of Information - Christian Bruns (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Economists usually think that rational voters have little incentives to acquire costly information. We present a theoretical model to show that, in contrast to this widely held belief, rational voters acquire considerable amounts of information if media technology is available because then they do not condition their informational decisions on being pivotal. The model also shows that the quality of media coverage is inefficiently low because voters have incentives to free-ride. Further, we show how the quality of information depends on the size of the electorate, the prior knowledge of voters and on the technology to produce information.
Keywords: D72; D83; H41; 330